A More Comprehensive Approach to the Neuroprotective Potential of Long-Chain Polyunsaturated Fatty Acids in Preterm Infants Is Needed—Should We Consider Maternal Diet and the n-6:n-3 Fatty Acid Ratio? - Klevebro, Susanna; Juul, Sandra E.; Wood, Thomas R. (Frontiers in Pediatrics, 2020)
There is growing evidence that long-chain polyunsaturated fatty acids (LCPUFAs) are of importance for normal brain development. Adequate supply of LCPUFAs may be particularly important for preterm infants, because the third trimester is an important period of brain growth and accumulation of arachidonic acid (n-6 LCPUFA) and docosahexaenoic acid (n-3 LCPUFA). Fatty acids from the n-6 and n-3 series, particularly, have important functions in the brain as well as in the immune system, and their absolute and relative intakes may alter both the risk of impaired neurodevelopment and response to injury. This narrative review focuses on the potential importance of the n-6: n-3 fatty acid ratio in preterm brain development. Randomized trials of postnatal LCPUFA supplementation in preterm infants are presented. Pre-clinical evidence, results from observational studies in preterm infants as well as studies in term infants and evidence related to maternal diet during pregnancy, focusing on the n-6: n-3 fatty acid ratio, are also summarized. Two randomized trials in preterm infants have compared different ratios of arachidonic acid and docosahexaenoic acid intakes. Most of the other studies in preterm infants have compared formula supplemented with arachidonic acid and docosahexaenoic acid to un-supplemented formula. No trial has had a comprehensive approach to differences in total intake of both n-6 and n-3 fatty acids during a longer period of neurodevelopment. The results from preclinical and clinical studies indicate that intake of LCPUFAs during pregnancy and postnatal development is of importance for neurodevelopment and neuroprotection in preterm infants, but the interplay between fatty acids and their metabolites is complex. The best clinical approach to LCPUFA supplementation and n-6 to n-3 fatty acid ratio is still far from evident, and requires in-depth future studies that investigate specific fatty acid supplementation in the context of other fatty acids in the diet.